A review on current understanding of pipeline circumferential stress corrosion cracking in near-neutral PH environment. (June 2023) - Shirazi, Hamed; Eadie, Reg; Chen, Weixing
Highlights: The interaction of applied and residual axial stresses dominates C-SCC occurrence. The corrosion fatigue mechanism explains the cracking of pipeline steels in C-SCC. Pipe bending, girth welding and soil movement can create residual axial stresses. The internal pressure contributes significantly to the cyclic nature of axial stress. Most C-SCC failures occur at bends in presence of Bourdon and Hydrodynamic stresses. Abstract: In recent years, pipeline failures attributed to circumferential stress corrosion cracking (C-SCC) in near-neutral pH environments were reported. The environmental conditions that led to C-SCC are similar to those associated with pipe axial transgranular near-neutral pH SCC (A-SCC), which is caused by groundwater in contact with the outer surface of the pipe steel at disbonded areas. C-SCC failures remain rare, but they are often unexpected and can create significant pipeline operation and safety hazards. In C-SCC, residual and axial stresses together, instead of hoop stress for A-SCC, play an important role. Stress from the internal pressure pushes on the pipe ends and make axial stress in the pipeline. On the other hand, the axial residual stresses, because of pipe bending, girth welding, and soil movement, can increase the magnitude of tensile stresses to a level that is prone to circumferential crack initiation and growth. Axial stresses have a cyclical nature because of internal pressure fluctuations. There are two exclusive stresses at pipe bends, which may explain why most of the C-SCC failures occur at them. These are the hydrodynamic stresses from the change in momentum of the moving fluid when it goes around a bend, and the Bourdon effect caused by the difference in the stress acting on the outside of the bend and the inside of the bend. These stresses also fluctuate with the fluctuation in the internal pressure and influence initiation and growth of C-SCC cracks. There is a need to carry out both numerical and experimental studies to quantify the susceptibility to C-SCC crack initiation and growth under various contributing factors potentially encountered during field operation. This paper will discuss details on how various stress factors and their combinations can affect different stages of the cracking mechanism, including surface corrosion and initiation of cracks, early-stage growth, dormancy, reactivation of dormant cracks, and crack growth. Moreover, the gaps in knowledge about C-SSC will be delineated. Finally, remedial actions are recommended to deal with the C-SCC threats.